Pengembangan Bahan Ajar Laju Reaksi Dengan Multipel Representasi Berbasis Inkuiri - Pahriah, Pahriah; Hendrawani, Hendrawani (Hydrogen: Jurnal Kependidikan Kimia, 2019)
This development aims to determine the characteristics and feasibility of multiple inquiry-based representation modules in the reaction rate material through the ADDIE stage (Analyze, Design, Development Implementation and Evaluation) developed by Thiagarajan. This research and development was carried out until the development stage with adjustments based on development needs. The assessment instrument used to determine the feasibility of the module is a questionnaire sheet. The module feasibility was assessed by 2 material experts, 1 media expert, 1 linguist, 1 colleague, 1 practitioner, and 10 students as subjects. Students involved in this study came from chemistry education study programs that had undergone basic chemistry courses through limited trials. The data on the value of the grievances obtained are still in the form of qualitative data and then processed into quantitative data. Quantitative data are analyzed for each aspect of the assessment. The final score obtained is converted to the level of product feasibility qualitatively with the guidelines according to the criteria of the assessment category. The results of expert validation showed the average percentage (a) of material experts was 84% with very feasible categories; (b) media experts 90% with very decent categories; (c) linguists 97% with very decent categories; (d) colleagues 79.6 categories worth%; (e) practitioners 86.4% are very decent categories. The average response of students to product development results 89.5% with a very feasible category. This shows that the modules developed are feasible to be used at the stage of large-scale trials.